Polyphenol-rich fraction of Thalassia hemprichii: dual enzyme inhibition, antioxidant capacity, and anti-inflammatory activity for diabetes management - Navni Rohatgi; Dilipan Elangovan; Vasugi Suresh; Mohammed Asif Hussein (Journal of Applied Pharmaceutical Research, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder marked by hyperglycemia and associated complications. Limitations of current therapies have driven interest in marine-derived bioactives, particularly polyphenols, for safer and multi-targeted interventions. Thalassia hemprichii, a tropical seagrass rich in phenolic compounds, remains underexplored for antidiabetic potential. Methodology: A polyphenol-rich fraction (PRF) was extracted from T. hemprichii leaves using sequential solvent extraction. FTIR spectroscopy was employed to identify functional groups. Total phenolic and flavonoid contents were quantified using spectrophotometric methods. In vitro antidiabetic activity was assessed by α-amylase inhibition (DNSA method) and α-glucosidase inhibition (pNPG assay), with acarbose as the reference, and anti-inflammatory and antioxidant assays were also performed. Results and Discussion: FTIR analysis confirmed the presence of hydroxyl, carbonyl, and aromatic groups, indicating the presence of phenolic compounds. PRF demonstrated dose-dependent inhibition of α-amylase (13.4–55.6%) and α-glucosidase (16.72–58.14%) at concentrations of 25–125 μg/mL, with IC₅₀ values comparable to acarbose. The inhibitory profile showed stronger activity against α-glucosidase and moderate suppression of α-amylase. In addition, PRF exhibited significant antioxidant (49.40–78.23%) and anti-inflammatory (40.78–75.02%) effects in a concentration-dependent manner (50–200 μg/mL). Conclusion: The polyphenol-rich extract of T. hemprichii exhibits notable dual-enzyme inhibition, indicating its potential to manage postprandial hyperglycemia while reducing gastrointestinal side effects. Its cytoprotective properties, including antioxidant and anti-inflammatory activities, further support its role in preventing diabetes-related complications. These findings highlight T. hemprichii as a promising candidate for nutraceutical or phytopharmaceutical development, meriting further in vivo validation and safety evaluation.